Comparison of Analgesic Effects of Nalbuphine and Buprenorphine on Caudal Ropivacaine in Children Undergoing Infraumbilical Surgeries - Kaur, Navdeep; Chinnappa, Jithendra; Iyer, Sadashivan S; Suresh, Govindswamy; Turai, Ashwini (Journal of Anaesthesia and Pain, 2025)
Introduction:Caudal anaesthesia is the most commonly performed regional anaesthesia in children. Opioids are the most commonly used additives to Local Anesthetics. Synthetic Opioid Agonist- Antagonists like Nalbuphine and Buprenorphine provide advantage of prolonging duration and quality of analgesia without risk of respiratory depression.OBJECTIVE OF THE STUDYTo study the effects of caudal nalbuphine or buprenorphine on postoperative analgesia produced by caudal Ropivacaine in children undergoing infraumbilical surgery.Materials and Methods Following Institutional Ethical Committee Clearance 54 ASA grade I and II children, aged 1-10 years scheduled for elective infra umbilical surgeries under General Anaesthesia with Caudal Epidural were randomly allocated using Computer Generated Random Number Tables into 3 groups R (Ropivacaine 0.2% 1ml/kg), RN (0.2% Ropivacaine with0.1mg/kg Nalbuphine) and RB (0.2% Ropivacaine with 3mcg/kg Buprenorphine). The time taken for first analgesic was noted and was compared between the groups.RESULTS A Total of 54 patients were enrolled for the study. Both the nalbuphine and buprenorphine provided good analgesia in the post operative period compared to plain ropivacaine group ( p<0.05) with higher incidence of side effects in group RB. CONCLUSIONAddition of Nalbuphine(0.1mg/kg) to caudal ropivacaine provides comparable duration of analgesia with caudal Buprenorphine and ropivacaine (3mcg/kg)with lesser incidence of side effects. KEYWORDSNalbuphine,  Ropivacaine, Buprenorphine, Caudal Epidural CTRI TRIAL REGISTERATION CTRI/2017/08/009445